Decolonizing design a cultural justice guidebook - Tunstall, Elizabeth (The MIT Press, 2023)
"Responds to the urgent call to decolonize design through powerful, incisive guidelines drawn from 15 years of lived experience. A transformative blueprint for repairing the harm caused by structural inequity through decolonizing not only our institutions, but also our thinking, and how to begin today"--Provided by publisher.